2018
DOI: 10.1590/s1980-6574201700si0093
|View full text |Cite
|
Sign up to set email alerts
|

Trends in television and computer/videogame use and total screen time in high school students from Caruaru city, Pernambuco, Brazil: A repeated panel study between 2007 and 2012

Abstract: -Aim: to analyze the pattern and trends of use of screen-based devices and associated factors from two surveys conducted on public high school students in Caruaru-PE. Methods: two representative school-based crosssectional surveys conducted in 2007 (n=600) and 2012 (n=715) on high school students (15-20 years old). The time of exposure to television (TV) and computer/videogames PC/VG was obtained through a validated questionnaire, and ≥3hours/day was considered as being excessive exposure. The independent vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…During the past few years, researches repeatedly showed that television time presented a decreasing trend, data from the Youth Risk Behaviour Surveillance and showed that exposure to TV of least 2 hr/day reduced from 1999 to 2007 (Lowry, Lee, Fulton, & Kann, ). At the same time, a recent study reported that children are main users of other electronic devices such as computer, smart phone, and video (Aros, Germano‐Soares, Silva, Silva, & Tassitano, ), and Silva et al () demonstrated that time spent on computer and video game increased from 2001 to 2011. The different types of screen may have different effects on childhood overweight/obesity.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few years, researches repeatedly showed that television time presented a decreasing trend, data from the Youth Risk Behaviour Surveillance and showed that exposure to TV of least 2 hr/day reduced from 1999 to 2007 (Lowry, Lee, Fulton, & Kann, ). At the same time, a recent study reported that children are main users of other electronic devices such as computer, smart phone, and video (Aros, Germano‐Soares, Silva, Silva, & Tassitano, ), and Silva et al () demonstrated that time spent on computer and video game increased from 2001 to 2011. The different types of screen may have different effects on childhood overweight/obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This non-association can also be related to the viewing distance from the TV, which is usually greater than other devices. The interaction pattern of allied devices including the use of social networking seems to impact the sleep quality and anxiety in adolescents (Aros, Germano-Soares, Silva, Silva, & Tassitano, 2017;Silva et al, 2014). For example, in a study conducted by Espinoza and Juvone (2011) with 268 young adolescents, it was found that 37% reported having lost sleep due to the use of social networking sites.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing use of computers and videogames by adolescents 116 , these electronic devices are not yet accessible to most Brazilian households 120 . Another aspect that can contribute to the greater variability of these components in Brazilian data might be social and income inequality 43,116,121 .…”
Section: Discussionmentioning
confidence: 99%